Effect of microchannel diameter on electroosmotic flow hysteresis - Lim, An Eng (2023)
Electroosmotic flow (EOF) commonly involves inhomogeneous fluids in practical applications. EOF hysteresis, which is defined as direction-dependent flow behavior, has been extensively investigated for dissimilar solution pair systems. Hitherto, there is no investigation being conducted to examine the effect of microchannel diameter on the hysteresis phenomenon. In this investigation, current monitoring experiments and finite element numerical simulations were performed to examine the intensification of the hysteretic behavior with reduction in the microchannel diameter. Three solution pairs were selected for the study, namely KCl–NaCl (dissimilar ionic species with similar concentration), NaCl and KCl (similar ionic species but different concentrations) solution pairs, with microchannels of 5 μm and 100 μm internal diameters. EOF hysteresis augmentation for reduced channel diameter (i.e., 5 μm microchannel) is due to the coupling effect of the resultant wider/tighter interfacial width and the minority pH-governing ion-driven hysteresis, which was earlier discovered to be the origin of EOF hysteresis. This investigation provides an appropriate understanding of the channel dimensional effect on EOF behavior involving multiple fluids, and the outcomes can potentially be implemented on chemical and biological microfluidic systems with adjustable throughput.